Strategic Development and the Effectiveness in Education Management of the Buddhist Scripture School Chinese Sects in the Changing Context - Wongyangpharsert, Phra Suthep; Vechcha, Prawet; Ouppinjai, Suwadee; Yawirach, Phoonchai (Ratchaphruek Journal, 2020)
The objective of this study was to develop the strategies for effective education administration and management of the Phrapariyatidhamma School, General Department, Chinese Sects in the Changing Context. The research methodology employed mixed-method approach sectioned into 4 stages. Stage 1: Collecting the qualitative data by means of interview concerning the circumstance of education administration and management of the Phrapariyatidhamma School, General Department, Chinese Sects. Stage 2 & 3: Collecting the qualitative data by means of focus-group discussion concerning the factors affecting the education administration and management the desired future scenario of the education administration and management of the Phrapariyatidhamma School, General Department, Chinese Sects, and Stage 4: Collecting the qualitative data by means of interview concerning the strategies for effective education administration and management of the Phrapariyatidhamma School, General Department, Chinese Sects. The target group involved 18 participants who were directors and teachers of Wat Muen Phutthawitthaya School, Wat Mangkorn Kamalawat Wittayalai and Wat Photithatra Wittayalai. The data analysis were employed by mean and standard deviation, and from tape-recording, and performed content analysis for summary. The results revealed 4 development strategies i.e. Strategy 1: Developing academic competence based on school curriculum comprising 5 projects. Strategy 2: Developing teachers and staff for professional competence comprising 3 projects. Strategy 3: Arranging facilities favorable to the learning comprising 3 projects. Strategy 4: Allocating modern information technology system comprising 4 projects.